Respon Pelanggan dalam Pembelian Online Produk Fashion di Zalora Indonesia - Rinaldi, Afdhol; Dhimas Hakim, Muhamad; Priscilla, Mahdalina; Gita, Widhy Zenia (Jurnal Rumpun Ilmu Ekonomi, 2023)
As technology advances, the ability to do business on the Internet also increases. Many people already enjoy online shopping. Apart from convenience, the prices of the products offered are relatively cheap or comparable to prices in traditional shops. One of the online stores that is popular among Indonesian people is Zalora. The aim of this research is to study the influence of consumer behavior on purchasing decisions. The findings ensuce that consumer behavior in the current technological era has a significant influence on purchasing decisions at Zalora Indonesia. This can also be seen from the results of the correlation coefficient test. Zalora The degree of relationship between consumer behavior and purchasing decisions in Indonesia is in the strong and unidirectional category with a result of 0.671. The influence of consumer behavior on purchasing decisions is 45.02% at Zalora Indonesia.